If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (10x)(10x) + 7 + -12 = 0 Remove parenthesis around (10x) 10x(10x) + 7 + -12 = 0 Remove parenthesis around (10x) 10x * 10x + 7 + -12 = 0 Reorder the terms for easier multiplication: 10 * 10x * x + 7 + -12 = 0 Multiply 10 * 10 100x * x + 7 + -12 = 0 Multiply x * x 100x2 + 7 + -12 = 0 Reorder the terms: 7 + -12 + 100x2 = 0 Combine like terms: 7 + -12 = -5 -5 + 100x2 = 0 Solving -5 + 100x2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 100x2 = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 100x2 = 0 + 5 100x2 = 0 + 5 Combine like terms: 0 + 5 = 5 100x2 = 5 Divide each side by '100'. x2 = 0.05 Simplifying x2 = 0.05 Take the square root of each side: x = {-0.223606798, 0.223606798}
| n^2+16n+64= | | n^2-9n+20= | | 34+54=11x+13 | | n^2+8n+12= | | graphy=2x-3 | | 2+-4= | | 7(3x+5y)= | | 15+3y=21 | | 2h+5=4h-9 | | 20x-10/5 | | x/-3=-6-(-4) | | 2x(2x/7)=(x/2)+(17/2) | | 3=-6(-4) | | 3(v+2)-v=2(v-1)+5 | | 4u=48 | | 3(w+2)+w=4(w-1)+10 | | (7x-5)(3x+3)= | | 77=11m | | (7x-5)(3x+3) | | m=1/2,b=0 | | 12p=60 | | 9x_=99 | | -7x^2+2x-3=0 | | 3x2x=24 | | 2x-2x/7=x/2+17/2 | | 60=12p | | 3m+17=6m+2 | | 3/4+-12 | | 12-a=25 | | -2/3r+2r=6/5r+14/5 | | -(9x+12)-4x | | 3(6z-1)-2(z+1)=5(z+1) |